Hydromorphic soils of the Río de la Plata coastal plain, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Río de la Plata coastal plain is a 5 to 10-km wide strip, extending along nearly 200 km on the right bank of this estuary, in northeastern Buenos Aires Province, Argentina. The climate is temperate humid (mean annual temperature and rainfall: 16.2ºC and 1040 mm). The coastal plain is covered with materials derived from intense sedimentation and littoral transport. These factors have interacted with marine ingressions and regressions occurred after the Last Glaciation Maximum. A large part of the coastal plain is covered with hydromorphic soils whose geochemical properties and response to environmental factors are not totally understood. The objectives of this work are: a) to describe the redoximorphic features of the soils; b) to analyze the temporal evolution of the main hydromorphic variables; and c) to establish the relationships between genetic factors and the hydromorphic variables. The evolution of Eh, pH, Fe2+, Mn2+ and moisture was analyzed monthly during two years in two representative soils: a Fluvaquent formed in fluviatile sands of the alluvial plain of Río de la Plata and a Natraquert developed in estuarine clays of a mudflat. Both soils exhibit different stability regarding their hydromorphic dynamics. The Fluvaquent is a very unstable system due to its coarse texture, which allows a rapid water movement from diverse sources (rain, phreatic water and floods), showing a heterogenous distribution of the redoximorphic features in the soil. The lowest horizon (2Cg) is nearly permanently saturated and reduced by phreatic water; it exhibits homogenous low-chroma colors and has the lowest Eh mean value. The overlying horizon (2Cxg), where the anoxic conditions fluctuate, has mottles and localized hardening due to the precipitation of Fe and Mn oxides, indicating oxidizing conditions during some part of the year. These changes are reflected rapidly in Eh values, but not in Fe2+ and Mn2+ contents, which involve physico-chemical equilibria that are not instantaneous. Floods affect mainly the two upper horizons and there is little influence of evapotranspiration. The Natraquert exhibits more stable geochemical conditions due to its clayey texture, which prevents a rapid oxygen access, even during summer when a short deficit period occurs. It has homogenous reduced colors in the matrix. This soil is affected by waterlogging without influence of floods, whilst the phreatic water only affects the deepest horizons. High Eh values and Mn2+ segregation are observed. Evapotranspiration has an influence on the upper horizons.